Integrasi Mind Mapping dalam Pembelajaran Bahasa Arab sebagai Pendekatan Visual-Inovatif di Pondok Pesantren Rahmatul Umam - Lalu Irfan Ridwan; Agung Setiyawan (Lembaga Yasin AlSys, 2026)
Although mind mapping has received attention in several previous studies, research that specifically discusses its integration into Arabic language learning in the pesantren environment remains limited. Arabic language proficiency is one of the main characteristics of santri, but learning processes that are still dominated by conventional methods tend to make it difficult for santri to understand, organize, and connect material concepts systematically. This study aims to examine the integration of mind mapping in Arabic language learning as a visual-innovative approach at Pondok Pesantren Rahmatul Umam. This study used a qualitative approach with a case study design. Data were collected through observation, interviews, and documentation involving fifteen santri, two Arabic language teachers, and one kitab class homeroom teacher selected through purposive sampling. The data were analyzed descriptively and analytically through the stages of data reduction, data display, and conclusion drawing. The results showed that the integration of mind mapping helped santri map the structure of Arabic language material, connect concepts, improve memory, and encourage active engagement in learning. Thus, this study contributes to the development of Arabic language learning methods that are more systematic, effective, and oriented toward improving santri’s conceptual understanding in the pesantren environment.